2017
DOI: 10.3389/fmicb.2017.02466
|View full text |Cite
|
Sign up to set email alerts
|

Improved Drought Stress Response in Alfalfa Plants Nodulated by an IAA Over-producing Rhizobium Strain

Abstract: The drought–stress response in plant involves the cross-talk between abscisic acid (ABA) and other phytohormones, such as jasmonates and ethylene. The auxin indole-3-acetic acid (IAA) plays an integral part in plant adaptation to drought stress. Investigation was made to see how the main auxin IAA interacted with other plant hormones under water stress, applied through two different growth conditions (solid and hydroponic). Medicago sativa plants nodulated by the Ensifer meliloti wild type 1021 (Ms-1021) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 56 publications
(67 reference statements)
2
48
0
4
Order By: Relevance
“…However, a few studies reported differences between cultivars in efficiency of using soil water (Dobrenz, Wright, Humphrey, Massengale, & Kneebone, 1969;Grimes, Wiley, & Shesley, 1992). Anatomical and morphological differences in growth types generally influence alfalfa water use and capability to tolerate water deficit or cold by expressing fall dormancy (Paquin & Mehuys, 1980), reducing leaf size (Jung & Larson, 1972), and deepening root elongation (Defez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, a few studies reported differences between cultivars in efficiency of using soil water (Dobrenz, Wright, Humphrey, Massengale, & Kneebone, 1969;Grimes, Wiley, & Shesley, 1992). Anatomical and morphological differences in growth types generally influence alfalfa water use and capability to tolerate water deficit or cold by expressing fall dormancy (Paquin & Mehuys, 1980), reducing leaf size (Jung & Larson, 1972), and deepening root elongation (Defez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ABA is considered to be an important messenger involved in the adaptive response of plants against abiotic and biotic stresses (Umezawa et al 2006). ABA and IAA can improve plant drought-stress tolerance (Sreenivasulu et al 2012, Defez et al 2017. In this study, there was a slight increase but no significant difference in IAA compared with the WW group during drought stress, which may be attributed to the complexity of IAA biosynthesis regulation or/and the uniqueness of rice LYPJ.…”
Section: Discussionmentioning
confidence: 56%
“…По-видимому, увеличение содержания цитокининов может частично смягчать негативное влияние стресса на фотосинтетическую активность и замедлять ускоренное старение листьев (36). О с м о л и т ы. Еще одной стратегией адаптации к засухе служит повышение синтеза осмолитов -растворенных в цитозоле веществ с низкой молекулярной массой, которые даже в высоких концентрациях не токсичны для растения (37)(38)(39). Осмолиты повышают вязкость цитоплазмы, поглощают активные формы кислорода и защищают макромолекулы от свободных радикалов, тем самым поддерживая целостность мембран и метаболическую активность тканей, что обеспечивает возобновление роста после улучшения водного режима (40)(41)(42).…”
unclassified
“…А н т и о к с и д а н т н ы е к о м п о н е н т ы. Системы антиоксидантной защиты включают как ферментный (СОД, каталазу, пероксидазу, аскорбат-пероксидазу, глутатион-редуктазу), так и неферментный (цистеин, редуцированный глутатион и аскорбиновую кислоту) компоненты (27,37,52). Установлено, что кроме каталазы, различных пероксидаз и пероксидоксинов (25,53,46), еще несколько ферментов вовлечены в процесс избавления от перекиси водорода и свободных радикалов: дегидроаскорбатредуктаза, монодегидроаскорбат-редуктаза, глутатион-редуктаза (31,54).…”
unclassified
See 1 more Smart Citation